2017
DOI: 10.1002/sdtp.11667
|View full text |Cite
|
Sign up to set email alerts
|

17‐3: Towards Flexible Glass: Ultra‐Thin Glass with Tight Dimensional Tolerance and High Strength Achieved by Ion Exchange

Abstract: Ultrathin aluminosilicate glass AS 87 eco, has been produced by SCHOTT proprietary downdraw hot-forming method as thin as 50 μm. A tight thickness tolerance of ± 10um, with a TTV <10 um across an area of 400×500mm, and a surface roughness smaller than 1 nm have been achieved in mass production. Compared with other ultrathin glass, the uniqueness of AS 87 eco lies in its the outstanding chemical strengthening performance, where the surface compressive stress can reach over 800 MPa after an ion-exchange process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…15,16 It possesses high potential for applications such as electronics, vehicles, lighting, and so on. [17][18][19] Their application of ultrathin glass is still in the category for manufacturing electronic devices and products. Recently, we developed a freestanding ultrathin glass film (UGF), which has the thickness of a few micrometers and can be directly bonded onto a substrate at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 It possesses high potential for applications such as electronics, vehicles, lighting, and so on. [17][18][19] Their application of ultrathin glass is still in the category for manufacturing electronic devices and products. Recently, we developed a freestanding ultrathin glass film (UGF), which has the thickness of a few micrometers and can be directly bonded onto a substrate at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Freestanding ultrathin glasses with the thickness of micrometers have been paid much attention in recent years due to their outstanding characteristics in terms of flexibility, transparency, surface smoothness, gas barrier capability, and so on 15,16 . It possesses high potential for applications such as electronics, vehicles, lighting, and so on 17‐19 . Their application of ultrathin glass is still in the category for manufacturing electronic devices and products.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the 2‐point bending test, fracture mostly occurs from the bottom side of the glass during bending under pen drop condition. The failure of the upper surface was thought to occur due to reverse bending that is induced by stress wave and indicated as second maximum stress in Figure 7 on the upper side of the glass, if the size of the surface flaws on the bottom surface, where maximum deformation and stress occurred, were relatively small or did not exist 27,32 . Thus, based on the high‐speed camera and FE simulation results in Figure 7, the fracture of the chemically strengthened UTG can be understood to indicate that the radial cracks were primarily generated by bending of the lower surface in the central area within a very short time.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies on the fracture behavior of UTG to improve impact resistance have been reported, except a few works on the chemical strengthening characteristics of UTG for foldable applications 26,27 and the fracture mechanism of bilayer structures with pristine UTG, via static, and dynamic indentation tests 28,29…”
Section: Introductionmentioning
confidence: 99%
“…This development has led to a strong demand for thinner display materials, including polymer films such as polarizer, as well as glass. Ultra-thin glass (ranging from 30 to 150 μm in thickness) has been proposed as one such materials [2] [3]. This material has a unique property, namely, it is as as flexible as polymers.…”
Section: Introductionmentioning
confidence: 99%